Pengaruh Pendampingan Suami Terhadap Penurunan Intensitas Nyeri Pada Ibu Bersalin - Supiani, Supiani; Herlyana, Baiq Herdina; Yusuf, Nurlathifah N; Siswari, Baiq Disnalia (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2024)
Labor pain is a physiological condition. This situation is an unpleasant feeling that occurs during the birthing process. Labor pain begins to appear in the first stage of labor, the latent phase and the active phase. The longer the pain is felt, the stronger it will be, the peak of the pain occurs in the active phase, where complete opening is up to 10 cm. The intensity of pain during labor will affect the psychological condition of the mother, the birthing process and the well-being of the fetus. To determine the effect of husband's assistance on reducing the intensity of first stage pain in mothers giving birth at the UPT BLUD Puskesmas Santong. The type of research used was an experimental questionnaire with the design chosen using a non-randomized control group posttest design. The sample was divided into 2 groups, namely 15 people in the intervention group and 15 people in the control group obtained using purposive sampling. The instrument in this research is an observation sheet. This research found that there was an effect of husband's assistance on reducing the intensity of pain in the 1st stage in women giving birth at the UPT BLUD Santong Health Center of the t test analysis showed tcount>ttable. There is an influence of husband's assistance on reducing the intensity of pain in the first stage in women giving birth at the UPT BLUD Santong Community Health Center.